2003
DOI: 10.1161/01.str.0000066309.06490.b8
|View full text |Cite
|
Sign up to set email alerts
|

Early Assessments of Dysphagia and Aspiration Risk in Acute Stroke Patients

Abstract: Background and Purpose-Dysphagia is common after stroke and is a marker of poor prognosis. Early identification is important. This article reviews the merits and limitations of various assessment methods available to clinicians. Methods-An electronic database search was performed of MEDLINE, EMBASE, and the Cochrane database using such terms as stroke, aspiration, dysphagia, and assessment; extensive manual searching of articles was also conducted. Results-Bedside tests are safe, relatively straightforward, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
225
1
22

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(252 citation statements)
references
References 57 publications
4
225
1
22
Order By: Relevance
“…According to Mathers-Schmidt and Kurlinski [9], clinicians may be influenced by research studies that highlight the profound limitation of the traditional bedside examinationÕs inability to reliably detect silent aspiration [4,22]. In contrast to the respondents in the study by Mathers-Schmidt and Kurlinski [9], however, all of the respondents to the patient scenarios in the current study indicated that they usually or always conduct a clinical/bedside evaluation before determining the need for an instrumental diagnostic procedure.…”
Section: Clinical Decision-makingmentioning
confidence: 79%
See 2 more Smart Citations
“…According to Mathers-Schmidt and Kurlinski [9], clinicians may be influenced by research studies that highlight the profound limitation of the traditional bedside examinationÕs inability to reliably detect silent aspiration [4,22]. In contrast to the respondents in the study by Mathers-Schmidt and Kurlinski [9], however, all of the respondents to the patient scenarios in the current study indicated that they usually or always conduct a clinical/bedside evaluation before determining the need for an instrumental diagnostic procedure.…”
Section: Clinical Decision-makingmentioning
confidence: 79%
“…Aspiration is caused by the entry of food or liquid into the airway below the true vocal folds [8]. It is well-documented in the literature that a profound limitation of the traditional bedside examination is its inability to reliably detect silent aspiration (when a patient aspirates with no outward clinical sign such as coughing/choking), because the pharyngeal phase of the swallow is not objectively assessed [4,22]. As mentioned previously, the result of a bedside screening examination generally helps the SLT to determine whether further, more objective instrumental assessment is warranted [22,23], so it is not surprising that respondents showed a high-percentage agreement in recommending an instrumental course of action (87.9%).…”
Section: Clinical Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that, six months after the stroke, deglutition abnormalities are present in 50% of such patients 9,13,14 .…”
mentioning
confidence: 99%
“…Studies making objective assessments through swallowing examinations have shown that the prevalence of aspiration may reach 55%, and that around 45% of the cases result in death 6,7 . Among the most frequent complications of dysphagia are increased mortality, pulmonary risks such as aspiration pneumonia, dehydration, malnutrition and long-term hospitalization 3,4,8,9 . Surveys have shown that the predictors of dysphagia in clinical assessments include older age, greater severity of stroke, wet vocal quality, abnormal palatal reflex, weak or absent cough, abnormal voluntary cough, coughing with swallowing and injury sustained in controlling secretions 9,10 .…”
mentioning
confidence: 99%